(untitled) (Research, Society and Development, 2024)
Introduction: Medicinal plants (MP) have been widely used in cosmetic products to harness their beneficial properties and promote skin and hair health and beauty. Mentha piperita Linnaeus, commonly known as peppermint, is an MP with refreshing, antiseptic, and stimulating properties, making it a valuable ingredient in a wide variety of cosmetic products. Objective: To analyze and synthesize the available scientific evidence on the topical use of Mentha piperita Linnaeus essential oil in relation to its therapeutic potential and safety. Methodology: The PICO strategy guided the search for evidence, gathering 24 articles published from January 2013 to May 2023 in the Virtual Health Library and PubMed databases. The variables analyzed were the therapeutic potential of Mentha piperita Linnaeus and the safety profile of cosmetics developed with Mentha piperita Linnaeus. Results: This review evaluated the published literature on the topical use of Mentha piperita Linnaeus essential oil, assessing its therapeutic potential and safety. Conclusions: Mentha piperita Linnaeus essential oil has therapeutic and aromatic properties, making it valuable in various industries. However, it is important to consider the risks associated with its use. To ensure consumer safety, it is necessary to follow usage recommendations, purchase the product from reliable suppliers, and be aware of possible adverse effects. It is essential to recognize individual differences and discontinue use if unwanted reactions occur.